PENDAMPINGAN PENGUATAN LITERASI DIGITAL MELALUI PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN BAGI GURU PAI SMA DI PAMEKASAN - Fathorrozy, Fathorrozy; Nurhayati, Sri; Hasan, Nor; Maghfiroh, Muliatul; Suwantoro; Yaqin, Ainul; Mannan, Abd.; Kutsiyyah; Sa’i, Mad (Collaborative: Jurnal Pengabdian Masyarakat, 2025)
This community service article aims to examine the implementation of Assistance in Strengthening Digital Literacy through Training on the Development of Learning Media for Islamic Education (PAI) Teachers at Senior High Schools in Pamekasan. The method used in this program is the PIJAR model, which consists of four stages: planning, organizing, implementation, and evaluation. The results of the training show that the implementation of the community service program with the theme "Assistance in Strengthening Digital Literacy through Training on the Development of Learning Media for Islamic Education Teachers at Senior High Schools in Pamekasan" was carried out successfully and was able to improve participants’ understanding and skills in developing learning media using Canva and ClassPoint. This, in turn, enables them to enhance the quality of their teaching. It is also hoped that their students will experience positive impacts in the classroom through the use of more interactive media.